Update on the Treatment of Metastatic Urothelial Carcinoma. (6th June 2018) - Bukhari, Nedal; Al-Shamsi, Humaid O.; Azam, Faisal
Abstract : Platinum-based combination chemotherapy has been the standard of care in the first-line treatment of metastatic urothelial carcinoma (mUC). Treatment of metastatic disease following progression on platinum-based regimens has evolved significantly in the last few years. Clinical trials are currently ongoing to determine how best to use and sequence these treatments. In this minireview, we will review current first-line treatment options in both cisplatin fit and cisplatin unfit patients and advances in first- and second-line treatments including chemotherapy and immunotherapy. This review reports key findings from the clinical trials especially highlighting the importance of PD-1 and PD-L1 inhibitors in the treatment of bladder/urothelial carcinomas.